Sustainable Development and Climate Resilience 2050: Evaluating Indonesia’s Environmental Legal Landscape - Situmeang, Ampuan; Silviani, Ninne Zahara (Universitas Islam Negeri Raden Fatah Palembang, 2024)
Climate change poses significant threats the continuity and resilience of the existing environment. Through the Climate Resilience 2050 agenda, all countries are expected to contribute to mitigating and limiting the effects of climate change, while reducing activities that have the potential to damage the Earth’s atmosphere. As a country endowed with rich environmental diversity, Indonesia must address these challenges and participate in global efforts to ensure a sustainable and livable environment for the future. This study uses normative legal research methods to analyze Indonesia’s legal readiness in the framework of making policies that can increase Climate Resilience 2050. Using a statutory and regulatory approach, this study finds that Indonesia has legal readiness in terms of basic norms to support policies that increase climate resilience, however, still has a normative void to support the implementation of climate resilience-oriented policies because the regulations regarding the application of basic environmental law norms are overly skewed towards facilitating business activities.